An autonomous role and consideration of electronic health systems with access control in developed countries: a review - Salji, Mohd Rafiz; Udzir, Nur Izura (The Science and Information Organization, 2023)
The electronic healthcare system (EHS) nowadays is essential to access, maintain, store, and share the electronic health records (EHR) of patients. It should provide safer, more efficient, and cost-effective healthcare. There are several challenges with EHS, notably in terms of security and privacy. Nonetheless, many approaches can be utilized to tackle it, and one of them is access control. Even though numerous access control models were presented, traditional methods of access control, such as role-based access control (RBAC), were extensively employed and are still in use today. Currently, the number of EHS equipped with access control keeps growing, and some previous works utilize RBAC only or an autonomous role. However, relying only on a role in todays advanced technology may jeopardize security and privacy. The previous work also has flaws because of using an ineffective instrument that is costly to maintain and will burden organizations, particularly in developed countries. In this paper, the background and emphasis on the challenges associated with an autonomous role in the EHS are discussed. Following that, this paper provides recommendations and analytical discussion on existing EHSs with access control mechanisms for securing and protecting EHR in developed countries. Finally, instrument information in the form of a SWOT analysis is recommended to replace the present instrument utilized by the previous work for a notion to the organizations in the developed countries to select the best environment for their future or upgrade EHS.